Simultaneous inversion of hypocentral parameters and structure velocity of the central region of Madagascar as a premise for the mitigation of seismic hazard in antananarivo - 358910 Rambolamanana, G.; Suhadolc, P.; Panza, G. F.; International Centre for Theoretical Physics (Miramare-Trieste : IAEA, 1995)
16